Determination of intensity level between selected traditional games among Z generation - Liza, Choo Morley (Universiti Sains Malaysia, 2014)
Physical inactivity can be associated with an increased variety of diseases, especially non communicable chronic diseases such as cardiovascular, hypertension and diabetes mellitus. Moreover, this could lead to a major consequence prevalence of overweight and obesity in Z generation (members of the generation of people born after 1995 or 2000s, who are confident user of new technology such as smartphones, tablets and wireless internet). Besides, there were numbers of Z generation whom did not meet the recommendation of moderate to vigorous physical activity (MVPA) to gain the health benefit. Traditional games could be an attractive alternative activitiy for the Z generations. Therefore, this study aims to determine the physical activity intensity in Z generation for the selected traditional games. Thus, primary school students (n=240), with (120 boys and 120 girls) aged 9 to 11 years old were recruited in this study. Parameter measured for the intensity determination was activity count per minute (CPM) by using accelerometer GTX3+. In addition to identify axes orientation involved in every traditional game using the same gadgets. Based on the two selected traditional games which were Baling Tin and Police and Thieves have found within moderate to vigorous physical activity (MVPA) level across the parameter measured. As for the activity count per minute (CPM) found that Baling Tin (944.59 ± 193.88) and Police and Thieves (952.48 ± 191.04). There was no significant difference of mean activity count per minute (CPM) between two games with p value = 0.751. Axis orientation showed that axis 1 in Baling Tin (51673.69 ± 13002.93) while Police and Thieves (42043.12 ± 12415.06) and there was significant difference of mean axis 1 between two games with p value < 0.001. In axis 2 was 53437.12 ± 11396.60 (Baling Tin) and 50430.45 ± 12146.55 (Police and Thieves). There was a significant difference of mean axis 2 between two games with p value = 0.049. Axis 3, Baling Tin (58785.59 ± 11109.20) and Police and Thieves (54060.79 ± 12238.46) also showed there was significant difference of mean axis 3 between two games with p value = 0.002. In conclusion, this study found that all the two selected traditional games exhibit MVPA type of activity and axis 3 of both traditional games reached the highest value, followed by axis 2 and axis 1 had the lowest value.